Mepolizumab and benralizumab in patients with severe asthma and a history of eosinophilic granulomatosis with polyangiitis - Desaintjean, Charlene; Ahmad, Kaïs; Traclet, Julie; Gerfaud-Valentin, Mathieu; Durel, Cecile-Audrey; Glerant, Jean-Charles; Hot, Arnaud; Lestelle, François; Mainbourg, Sabine; Nasser, Mouhamad; Seve, Pascal; Turquier, Ségolène; et al. (Frontiers in Medicine, 2024)
Introduction Asthma associated with eosinophilic granulomatosis with polyangiitis (EGPA) is often severe and corticosteroid-dependent, leading to significant morbidity. Mepolizumab and benralizumab are humanized monoclonal antibodies targeting interleukin 5 (IL-5) and its receptor, respectively. They have been shown to be effective in steroid-sparing in patients with severe eosinophilic asthma. Objective Our aim was to evaluate the efficacy and safety of mepolizumab and benralizumab prescribed for severe asthma in patients with EGPA under “real-world” conditions. Methods This was a retrospective analysis of patients with EGPA and persistent asthma who received either mepolizumab 100 or 300 mg administered every 4 weeks, or benralizumab 30 mg administered every 4 weeks for the initial 3 injections and followed by an injection every 8 weeks thereafter, whilst combined with oral glucocorticoids. The follow-up every 6 ± 3 months included an assessment of clinical manifestations, pulmonary function tests and eosinophil cell count. The primary outcome was the proportion of patients at 12 months receiving a daily oral dose of prednisone or equivalent of 4 mg or less with a BVAS of 0. Results Twenty-six patients were included. After 12 months of treatment with mepolizumab or benralizumab, 32% of patients met the primary outcome and were receiving less than 4 mg of prednisone per day with a BVAS of 0. The median dose of prednisone was 10 mg per day at baseline, 9 mg at 6 months, and 5 mg at 12 months (p ≤ 0.01). At 12 months, 23% of patients were weaned off corticosteroids, while an increase or no change in dose was observed in 27% of patients. The median eosinophil count was significantly reduced from 365 cells/mm3 to 55 cells/mm3 at 6 months and 70 cells/mm3 at 12 months, respectively. No significant change was observed in FEV1. After 12 months of treatment, 14% of patients had had an average of 1 exacerbation of asthma, compared with 52% of patients before baseline. The tolerability profile was favorable. Conclusion In this real-world study in patients with severe asthma and a history of EGPA asthma, mepolizumab and benralizumab had a significant steroid-sparing effect and reduced asthma exacerbation, but no significant effect on lung function.